If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -4) = 3x + 21 Reorder the terms: 6(-4 + 3x) = 3x + 21 (-4 * 6 + 3x * 6) = 3x + 21 (-24 + 18x) = 3x + 21 Reorder the terms: -24 + 18x = 21 + 3x Solving -24 + 18x = 21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -24 + 18x + -3x = 21 + 3x + -3x Combine like terms: 18x + -3x = 15x -24 + 15x = 21 + 3x + -3x Combine like terms: 3x + -3x = 0 -24 + 15x = 21 + 0 -24 + 15x = 21 Add '24' to each side of the equation. -24 + 24 + 15x = 21 + 24 Combine like terms: -24 + 24 = 0 0 + 15x = 21 + 24 15x = 21 + 24 Combine like terms: 21 + 24 = 45 15x = 45 Divide each side by '15'. x = 3 Simplifying x = 3
| D=123 | | (5X+3(2X))=4(10+1) | | 3(X)+X=2(4+4) | | 3x^2-10x-16=0 | | 7(x-5)+14=17 | | 3(5X)+X=8*2 | | x^2+-4x-1=0 | | X+2X=5(4)+1 | | 0.53x+4=0.513 | | 115.2-75.475.4100= | | 7x=120 | | y=-0.25(-3.2)-2 | | 22t=42 | | 24=-6(-3.2)+4y | | -18+4= | | 2x^3+4x^2+1= | | (180)-25= | | 24=-6x-4(-0.25x-2) | | S+3P=R | | 9-8x=73-36x | | 3(2x-4)-2(2x+3)= | | 24=-6x-4(0.25x-2) | | 21.792/0.96= | | 3x+72=180 | | 30-11=c | | y-96=23.75x-2+16y | | x+30=180 | | (-4.2)(-6.8)= | | 7n+8=78 | | 15-(-4)=d | | 10x+4=11x+2 | | (-16)-(-42)= |